Competency Analysis of Evaluation of Technology-Based Learning in Elementary Teachers in the City of Surakarta - Hasan Mahfud; Fadhil Purnama Adi; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2019)
The purpose of the service is to train elementary school teachers to have the competence to make Technology-Based Learning Evaluation Instruments for Elementary Teachers in the City of Surakarta. In addition to training teachers, this service also aims to analyze teacher competencies in the Technology-Based Learning Evaluation Instrument for Elementary Teachers in Surakarta. The subject of this service is an elementary school teacher in the city of Surakarta. The method used in this service starts with Workshop, Practice, and Implementation. In conducting this training, the subjects were asked to take a test related to the preparation of Technology-Based Learning Evaluation Instruments for Elementary Teachers in the City of Surakarta. Analysis of the data used is pre-test and post-test. The result of this activity is that there is an increase in the knowledge and understanding of teachers regarding the preparation of Technology-Based Learning Evaluation Instruments for Elementary Teachers in the City of Surakarta